PENERAPAN EDUTECH MELALUI DIGITAL MARKETING PADA SANTRI DI PESANTREN SIROJUL HUDA - Aryani, Lina; Matondang, Nurhafifah; Sufyati, Sufyati (LPPM Universitas Bina Bangsa, 2024)
The large role of MSMEs in the growth of the Indonesian economy. The results of products that have been produced are better known to the public, so it is necessary to immediately carry out marketing, both conventional marketing and digital marketing. Digital marketing is a promotional activity for a brand or product using digital media connected to the internet. Partners are students at the Sirojul Huda Islamic Boarding School which is located in East Bogor District, Bogor City. There are several obstacles to the chosen object, such as the students have never received additional knowledge about how to start a business and the application of technology as a marketing medium. PKM activities aim to increase knowledge of marketing technology using digital media for the students of Pondok Sirojul Huda. The method of implementing service is carried out in several stages, namely preparation, implementation, evaluation and reporting. The results of the service activities provide insight for the students so that they are better prepared to determine their business and make it easier for the students to market their products through digital marketing. The conclusion of this service activity is providing new knowledge and skills for students in digital media